1999
DOI: 10.1159/000016503
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries in Pre–School Children: Associations with Social Class, Toothbrushing Habit and Consumption of Sugars and Sugar–Containing Foods

Abstract: This project examined the relative significance of dietary sugars, toothbrushing frequency and social class as predictors of caries experience (caries vs. no caries) among 1,450 British pre–school children who took part in the National Diet and Nutrition Survey. This cross–sectional survey was based on a representative sample of children aged 1.5–4.5 years studied in 1992/3. Children were classified into four groups according to social class and toothbrushing habit. Diet/caries associations were examined for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
134
5
21

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(173 citation statements)
references
References 22 publications
(39 reference statements)
13
134
5
21
Order By: Relevance
“…Hinds & Gregory (1995) reported no relationship between absolute levels of NME sugars or total sugar-containing foods and caries in a representative sample of 1450 UK pre-schoolchildren. Amount and frequency of non-chocolate confectionery were the only dietary variables related to caries in this study, but even these associations failed to reach signi®cance in children with good oral hygiene (Gibson & Williams, 1999).…”
Section: Guidelines For Sugar Consumption In Europe Chs Ruxton Et Alcontrasting
confidence: 59%
See 1 more Smart Citation
“…Hinds & Gregory (1995) reported no relationship between absolute levels of NME sugars or total sugar-containing foods and caries in a representative sample of 1450 UK pre-schoolchildren. Amount and frequency of non-chocolate confectionery were the only dietary variables related to caries in this study, but even these associations failed to reach signi®cance in children with good oral hygiene (Gibson & Williams, 1999).…”
Section: Guidelines For Sugar Consumption In Europe Chs Ruxton Et Alcontrasting
confidence: 59%
“…In a comparison of high and low caries groups (Jones et al, 1996), the average frequency of`sugar episodes' was around 12 ± 14 in the high caries group and 3 ± 5 in the low caries group. Eating frequency (excluding drinks) in caries free pre-school children ranged from 4 ± 7 times per day in the McMahon et al (1993) study, while in the Gibson & Williams (1999) study of preschoolers, the median for consumption of sugar-containing foods was four times per day. These studies challenge the assumption that sugar should be kept to mealtimes, that is three times per day, since a frequency of eating which exceeds this would appear compatible with little or no dental caries.…”
Section: Guidelines For Sugar Consumption In Europe Chs Ruxton Et Almentioning
confidence: 93%
“…Neste estudo, não foi observada nenhuma associação entre consumo de açúcar e cárie precoce, contrariando o observado em outros estudos 17,18,29,39,40,41,42 . Sendo, ainda, essa associação considerada, por alguns autores 43,44 , como incontestável.…”
Section: Discussionunclassified
“…[4][5][6][7][8][9][10][11][21][22][23][24][25] Lower socio-economic groups in the United States have been found to have high levels of dental caries. 10 Children living in deprived wards (Jarman score 2.5 or greater) in Sheffield, England were one-and-a-half times more likely to have experienced decay than those from non-deprived wards.…”
Section: Deprivationmentioning
confidence: 99%
“…3,4,[6][7][8][9][10][11][12][23][24][25]31,33 This study has found evidence that parents who live in deprived areas have statistically less chance of answering questions correctly about dental knowledge and giving positive answers to questions to determine dental attitude. The evidence provided by this paper that those from deprived areas have lower dental knowledge levels and less positive dental attitudes indicates that these factors may be associated with the behaviours that are involved in caries aetiology.…”
Section: Deprivationmentioning
confidence: 99%